Harnessing Virtual Mom Power: Process and Outcomes of a Pilot Telehealth Adaptation of a Multifamily, Attachment-Based Intervention. (2nd January 2022) - Gray, Sarah A. O.; Moberg, Stephanie A.; Obus, Elsia A.; Parker, Victoria; Rosenblum, Katherine L.; Muzik, Maria; Zeanah, Charles H.; Drury, Stacy S.
ABSTRACT: The COVID-19 pandemic and mitigation strategies amplified racial and income-based health disparities, profoundly shifted family life, and altered delivery systems for support services. We report pilot data from a telehealth adaptation of Mom Power, an evidence-based, attachment-informed multifamily preventive intervention (clinicaltrials.gov: NCT04241913). We implemented an adaption of Virtual Mom Power (VMP) with a group of economically marginalized, predominantly Black mothers and their young children ( n = 9) in New Orleans, an early COVID-19 hotspot with an entrenched history of structural racism and trauma. We outline our approach to adaptation of curriculum and service delivery, using a trauma-informed lens. Maternal reports of maternal and child functioning from pre- to post-intervention were consistent with improvements in maternal depressive and post-traumatic stress symptoms and child competence, comparable to outcomes from in-person trials. Feasibility and acceptability data were strong. Preliminary results and reflections on process suggest that telehealth service delivery of a multifamily preventive intervention, with attention to decreasing barriers to online access and consideration of culture and context, facilitated engagement while maintaining fidelity and effects on intervention targets. Future research using larger samples, randomized controlled design, and multi-method assessment should continue to guide dissemination of reflective, group-based telehealth parenting programs.